2023
DOI: 10.1186/s12879-023-08237-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carbapenemase-producing Enterobacteriaceae from human clinical samples in Ethiopia: a systematic review and meta-analysis

Abstract: Introduction Carbapenemase-producing Enterobacteriaceae are by far the most public health and urgent clinical problems with antibiotic resistance. They cause longer hospital stays, more expensive medical care, and greater mortality rates. This systematic review and meta-analysis aimed to indicate the prevalence of carbapenemase-producing Enterobacteriaceae in Ethiopia. Methods This systematic review and meta-analysis was conducted based on Preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…63,64 A systematic review and meta-analysis showed 5.4% pooled prevalence of carbapenemase-producing Enterobacterales, with high prevalence in Central Ethiopia. 65 Recent data reports bla KPC , bla NDM , and bla OXA-48 from clinical isolates of Enterobacterales in Ethiopia. 66,67 Carbapenemase encoding genes, bla NDM , and bla OXA−48 are becoming the dominant carbapenemase variants in E. coli strains.…”
mentioning
confidence: 99%
“…63,64 A systematic review and meta-analysis showed 5.4% pooled prevalence of carbapenemase-producing Enterobacterales, with high prevalence in Central Ethiopia. 65 Recent data reports bla KPC , bla NDM , and bla OXA-48 from clinical isolates of Enterobacterales in Ethiopia. 66,67 Carbapenemase encoding genes, bla NDM , and bla OXA−48 are becoming the dominant carbapenemase variants in E. coli strains.…”
mentioning
confidence: 99%
“…A 2023 study revealed that of 183 diarrheal pathotype E. coli isolated from children, 4 (2.2%) were CPE [70], while another study evaluating GNB isolated from blood cultures revealed prevalences of 25.1% for CP-GNB and 5.6% for MBL producers among 231 GNB (179 Enterobacterales), with 2% CPE in the studied population [71]. A systematic review from 2023 reported an overall 5.44% pooled prevalence of CPE in Ethiopia, ranging from 2.24% in 2015-2016 to 17.44% in 2017-2018 and from 1.65% in the southern region to 6.45% in Central Ethiopia [72].…”
Section: Resultsmentioning
confidence: 95%
“…In previous studies conducted in Ethiopia, the rate of carbapenem resistance among Gram-negative rods was low ranging 1.7–15.1% ( Misha et al, 2021 ; Tekele et al, 2021 ; Seman et al, 2022 ; Tilahun et al, 2022 ; Alemayehu et al, 2023 ). However, our findings showed an increase in resistance to carbapenems (18.6%).…”
Section: Discussionmentioning
confidence: 92%
“…Such infections are major concerns for critically ill patients, immunocompromised individuals, and those with comorbidities ( Aleidan et al, 2021 ; Di Carlo et al, 2021 ). In resource-constrained countries, including Ethiopia, the public health impact is even worse due to the lack of reserve treatment options ( Alemayehu et al, 2023 ; Beshah et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%